The Absorption of Needle-Free Insulin Aspart Through Jet Injector in Different Body Parts of Healthy Individuals - Pan, Qi; Zhang, Lina; Gu, Aimin; Yu, Dongni; Wang, Xiaoxia; Zhou, Yan; Guo, Lixin (Frontiers in Endocrinology, 2022)
The absorption of needle-free fast-acting insulin injected into different body parts of healthy male subjects was studied in an attempt to provide clinical guidance for diabetic patients who take needle-free insulin injections in terms of providing reference in the clinical guidance regarding the correct use of needle-free insulin injection among diabetic patients. This randomized, open-label, cross-over trial was conducted on eight healthy adult male volunteers, in which the skin thickness at three injection sites (abdomen, upper arm, and thigh), the time to peak, peak rate, and area under the glucose infusion rate (GIR) curve of plasma insulin were measured through the hyperinsulin-normal glucose clamp test after the injection of insulin aspart with a needle-free syringe at three different sites to analyze the correlation between insulin absorption index at different injection sites and skin thickness. The values of the skin thickness of abdomen, upper arm, and thigh measured by ultrasonic wave were 2.45±0.34mm, 2.18±0.50mm and 1.93±0.55mm, respectively. There was a significant difference between the skin thickness of abdomen and thigh (P=0.014). The hyperinsulin-normal glucose clamp model was successfully established for each subject. 0-2h after injection of insulin aspart with needle-free syringes, the area under GIR-time curve of abdomen, upper arm, and thigh were 29400.75±2645.00mL, 30230.50± 4937.87mL, and 30179.63± 6188.57mL, respectively. There was no significant difference in the area under GIR curve between any two injection sites (P>0.05). The time to peak of GIR at different injection sites was 38.68±13.57 min in abdomen, 40.86±12.70 min in upper arm and 37.03±13.29 min in thigh, respectively, in which no significant difference was found between each two of them (P>0.05). The GIR curve after injection at the three different sites was consistent with each other. There was no significant difference in insulin absorption after the injection of insulin aspartate into abdomen, upper arm, and thigh with needleless syringe in healthy male adult volunteers, and there was no correlation between skin thickness at the injection site and insulin absorption. Injection sites did not affect the absorption of insulin in needle-free injection.